Contributions of Nursing to the Education and Promotion of Self-Care in Patients with Intestinal Ostomy: an Integrative Review - Isadora Martins de Pereira; Taiane de Oliveira Vieira; Felipe Kohl Hemsing; Elisiane de Oliveira Machado; Rejane Silveira Campos; Tatiane Gomes da Rosa Coelho (LPPM STIKes Muhammadiyah Ciamis, 2026)
Purpose: To identify in the literature the contributions of nursing in the education and promotion of self-care for patients with intestinal ostomy. Methods: This study is an integrative literature review conducted between April and June 2025, using the following databases: Virtual Health Library (BVS) and PubMed. To refine the search for studies, the descriptors